Modified Architecture and Innovative Algorithm for Story Prioritization in Scrum Framework to Aid Product Owner - Kalyani, Darshita; Mehta, Devarshi; Sajja, Priti (International Journal of Computer Sciences and Engineering, 2020)
Agile has emerged as the most popular approach to project management because of its iterative and flexible nature. It is described by a prominence on responding to changes. There are various prominent agile frameworks used by the industries and scrum is one of it. This paper focuses on the detailed overview of agile scrum framework. It elaborates the challenges / limitations in scrum implementation. The point of convergence of the paper is proposing the algorithm-based remediation for the story prioritization process of scrum framework. The proposed framework also confronting the problem of scope creep faced by scrum squad. The targeted audience is professionals who are involved in scrum project management methodology.